2014
DOI: 10.1039/c4dt01683a
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependent iodide oxidation by MLCT excited states

Abstract: The metal-to-ligand charge transfer (MLCT) excited states of two related heteroleptic Ru(ii) compounds [Ru(bpy)2(deeb)](2+) and [Ru(bpy)2(deebq)](2+), where bpy is 2,2'-bipyridine, deeb is 4,4'-(CO2CH2CH3)2-2,2'-bipyridine and deebq is 4,4'-(CO2CH2CH3)2-2,2'-biquinoline, were characterized in fluid acetonitrile by temperature dependent photoluminescence spectroscopies as well as quenching by iodide ions. Photoluminescence emanates from a manifold of thermally equilibrated excited states referred to as the thex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…In particular, they found that this enhanced delocalization increased the charge-transfer distance and therefore increased Δμ . Some evidence for delocalization over diethyl ester functional groups in the 4,4′-position has also been reported for [Ru­(bpy) 2 (deeb)] 2+ , where deeb = 4,4′-(CO 2 Et) 2 -2,2′-bipyridine . To investigate whether a similar enhancement of excited-state delocalization occurs to a greater extent for RuLP or RuLC, excited-state properties were determined for both complexes in acetonitrile solutions (Table ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In particular, they found that this enhanced delocalization increased the charge-transfer distance and therefore increased Δμ . Some evidence for delocalization over diethyl ester functional groups in the 4,4′-position has also been reported for [Ru­(bpy) 2 (deeb)] 2+ , where deeb = 4,4′-(CO 2 Et) 2 -2,2′-bipyridine . To investigate whether a similar enhancement of excited-state delocalization occurs to a greater extent for RuLP or RuLC, excited-state properties were determined for both complexes in acetonitrile solutions (Table ).…”
Section: Discussionmentioning
confidence: 95%
“…41 Some evidence for delocalization over diethyl ester functional groups in the 4,4′-position has also been reported for [Ru(bpy) 2 (deeb)] 2+ , where deeb = 4,4′-(CO 2 Et) 2 -2,2′-bipyridine. 42 To investigate whether a similar enhancement of excited-state delocalization occurs to a greater extent for RuLP or RuLC, excited-state properties were determined for both complexes in acetonitrile solutions (Table 2). Comparison of the photophysical properties of RuLP and RuLC did not reveal anomalously different radiative rate constants or lifetimes for either sensitizer molecule.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Hence in a standard quenching experiment, bromide first quenched, then enhanced, and then had no further influence on the excited state. This behavior is highly unusual particularly since it has been reported that both bromide and iodide typically quench this and related excited states in a manner expected and compliant with the Stern–Volmer model. , For bromide oxidation a strong photo-oxidant is necessary, and replacing the bpz ligands with 2,2′-bipyridine in [Ru­(deeb)­(bpz) 2 ] 2+ resulted in an excited state that did not oxidize bromide . To better understand the ion-pairing behavior, 1 H NMR and computational methods were utilized to quantify the detailed nature of the ground-state ion pairs and the influence on excited-state electron transfer as described below.…”
Section: Discussionmentioning
confidence: 98%
“…On the time scale of photoluminescence measurement, the emission quenching of Ru1 and Ru2 by oxygen in the absence and presence of DNA conforms to the Stern−Volmer equation. 55 However, as depicted by Figure 1, Ru1 can bind to the groove surface of DNA to induce the B-to-Z conformation transition, resulting in the Z-DNA stabilized by Ru1. Because the Z-DNA is quite different from the B-DNA, in which B-DNA has major and minor grooves with widths of 1.17 and 0.57 nm, and Z-DNA only shows basically consistent minor grooves with B-DNA, 56 the oxygen binding rates across the two kinds of conformational DNA would be different.…”
Section: Methodsmentioning
confidence: 99%